"One country, ten systems" – The use of different licensing systems in Norwegian aquaculture. (March 2022) - Hersoug, Bjørn
Abstract: Licensing has been a key instrument in the management of Norwegian aquaculture.This article reviews the licensing regime right from the start in 1973 to the present.Originally there was one licensing regime for commercial production of salmon and trout, while today there are ten different systems. The article reviews these ten systems, with particular emphasis on the special purpose licenses, most often created on request from the industry. The green licenses as well as development licenses are described more in detail, while licenses for land-based and offshore production are also included. While the special purpose licenses no doubt have served collective needs in the industry, such as education, research and innovation, they have also acted as backdoor to cheaper licenses. (The ordinary commercial licenses now are traded in the range of USD 15–20 million for a standard license of 780 tons of maximum allowable biomass (MAB)). Their effects on the ordinary license system, where growth is now regulated by the traffic light system, seem to be largely underestimated. In spite of turning the allocation of licenses into a more objective process, there is still a large degree of political and administrative discretion involved. The complete system has over time become very complicated and difficult to control. Attempts of reforming the system have so far largely been unsuccessful. The article ends by describing various reform proposals and concludes with some generic lessons. Highlights: The licensing regime has increased from one system to ten different systems in the period 1973–2021. Originally the main focus was on who should be allocated a license, while later changed to how farming was done. Special purpose licenses have proved to be "a back door" to cheaper licenses. The effects of the special purpose licenses on the ordinary system (the traffic light system) seem largely underestimated. The high price of ordinary commercial licenses (at sea) has driven the demand for new license schemes, such as land-based and offshore marine aquaculture.